Infrared detectors : papers presented at a meeting of the U.S. Speciality Group on Infrared Detectors - Moss, T. S. (Trevor Simpson) (Infrared physics, 1976)
Infrared Detectors is a collection of papers presented at a meeting of the U.S. Speciality Group on Infrared Detectors and deals with a variety of topics related to infrared detectors, such as PbSnTe diodes and detectors, charge coupled devices (CCD), photodiodes, and HgCdTe photoconductive detectors. This text has 11 chapters; the first of which investigates the effects of ionizing radiation on CCDs in order to assess their signal processing advantages in a high natural (Van Allen belt) or artificially induced radiation environment. Attention then turns to defects suffered by n-type HgCdTe du.